(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
The study was conducted in the agricultural season 2016-2017 in the village of Dweir Raslan in Tartous governorate where three dates for planting (20 November - 10 December - 1 January) were used for three densities (60 - 70 - 90 plants / m 2 ) The experiment was designed in a split blok desing Where the planting dates once occupied the main pieces and the plant density occupied the dissected pieces to show the effect of planting dates and plant density on some phenotypic yields of white lupine plant and their effect on some productive crops (number of pods / plant - 100 g seed weight - seed yield kg / h) and percentage of protein in seeds. The results showed that the dates of the late dates (January 1) were superior to those of the rest of the studied dates in the bacurian form in flowering and maturity. The average number of days to reach flowering was 10.6% (46.6 days). The average number of days to reach maturity (158.3 days) The average date (November 20) in the number of pods per plant with an average of 10.5 horns / plant and the weight of the dry seeds in the unit area at an average of 2355.3 kg / e and the percentage of protein in seeds was 37.7% As for the plant density, the density exceeded 90 plants / m 2 in the primordial characteristics of flowers and maturity and surpassed plants For the density of 70 plants / m² in the weight of the seeds dry air in the unit area at an average of (2432 kg / e) superior in the productivity of seed in the unit area on the rest of the densities studied and also exceeded the density of 60 plants / m 2 in the number of pods / plant average (11.7 horn / Plant) and the weight of the 100 seeds with an average (32.11 g). As for the interaction between the dates of cultivation and plant density, there were significant differences between the averages of all studied exercises except protein. نفذ البحث في الموسم الزراعي 2016-2017 في قرية دوير رسلان التابعة لمحافظة طرطوس حيث تم استخدام ثلاث مواعيد للزراعة (20 تشرين الثاني – 10 كانون الاول – 1 كانون الثاني) ثلاث كثافات (60 – 70 – 90 نبات/م²) وصممت التجربة بطريقة القطاعات المنشقة حيث شغلت مواعيد الزراعة القطع الرئيسية و شغلت الكثافة النباتية القطع المنشقة لمرة واحدة. لبيان تأثير مواعيد الزراعة و الكثافة النباتية على بعض الصفات الفينولوجية لنبات الترمس الابيض و تأثيرها على بعض الصفات الانتاجية (عدد القرون/نبات – وزن الـ100 بذرة غ – الغلة البذرية كغ/ه) وكذلك النسبة المئوية للبروتين في البذور. أظهرت النتائج تفوق نباتات الموعد المتأخر(1 كانون الثاني) على نباتات بقية المواعيد المدروسة في صفة الباكورية في الازهار و النضج حيث بلغ متوسط عدد الايام للوصول الى ازهار 10 % (46.6 يوم) اما متوسط عدد الايام للوصول للنضج (158.3 يوم) كما تفوقت نباتات الموعد المبكر (20 تشرين الثاني) في صفة عدد القرون على النبات الواحد بمتوسط (10.5 قرن/نبات) و في صفة وزن البذور الجافة هوائيا في وحدة المساحة بمتوسط (2355.3 كغ/هـ) كما تفوقت في نسبة البروتين في البذور بمتوسط (37.7 %) اما بالنسبة للكثافة النباتية فقد تفوقت الكثافة 90 نبات/م² في صفة الباكورية في الازهار و النضج و تفوقت نباتات الكثافة 70 نبات / م ² في صفة وزن البذور الجافة هوائيا في وحدة المساحة بمتوسط (2432 كغ/هـ) متفوقة في الانتاجية البذرية في وحدة المساحة على بقية الكثافات المدروسة كما تفوقت الكثافة 60 نبات/م² في عدد القرون/ نبات بمتوسط (11.7 قرن/نبات) و وزن الـ100 بذرة بمتوسط (32.11 غ) اما بالنسبة للتداخل بين مواعيد الزراعة و الكثافة النباتية فقد وجدت فروقات معنوية بين متوسطات كافة الصفات المدروسة ماعدا نسبة البروتين.